A união dos estudantes secundaristas de Patos de Minas (UEP/MG): militância e formação cidadã e político-partidária (1958 a 1971) - Silva, Geenes Alves da (2009)
This work focuses on the secondary student movement in Patos de Minas/MG, specifically on the Patos de Minas Students Union (UEP), from 1958, year of its inauguration, until 1971, when the institution went through an internal crisis. In the beginning of this research, we realized that there were not available works focusing on student actions in the urban centers in Brazil within that time. That was a rich period of the national history, in which contradictions became visible in utopias and projects of an incongruent world. At the same time, the developing movement of students lived along with the low indexes of school education. To historically describe the student movement of Patos de Minas, we used primary sources, such as: the Statute of the institution, its inauguration protocol, journals of school unions, the draft texts of radio program, called A Hora do Estudante . We made interviews with the activists of the time, picking out the ex-leaders and administrators of the institution. The political stand of the UEP against communism and its actions in the military movement as well as the Church participation empowered us to think that the student movement of Patos de Minas was progressive-conservative. Contradictory, if we compare it with other great urban centers, but coherent within the reality which allowed it to be, that is, with the private world of Minas Gerais, which was Patos de Minas at that time.